Brachystelma annamacharyae sp. nov. (Apocynaceae) from the Seshachalam hills of Andhra Pradesh (India). (29th March 2016) - Prasad, K.; Prasanna, P. V.; Meve, Ulrich; Rao, M. Sankara; Thulasaiah, T.
Abstract : Brachystelma annamacharyae K. Prasad, Prasanna, Meve, Sankara Rao & T. Thulasaiah, a new species from the Sanipaya beat in the Seshachalam hills in Andhra Pradesh (India) is described and illustrated. The new species shares the long filiform pedicels, reflexed corolla lobes and an exposed corona with its most closely allied species, B. swarupa from Kerala and B. ciliatum from Karnataka and Andhra Pradesh, but differs from these by generally dwarfed and completely glabrous vegetative parts and uniflowered inflorescences, therby resembling certain South African species of the genus.